Transcatheter closure of a residual leak after surgical left atrial appendage ligation - Wunderlich, Nina C.; Franke, Jennifer; Küx, Harald (European heart journal - cardiovascular imaging, 2019)
A 79-year-old man with long-lasting atrial fibrillation underwent surgical mitral and tricuspid valve repair and left atrial appendage (LAA) ligation with a dou
Online publish-ahead-of-print 18 February 2019
Gesehen am 21.11.2019